Unraveling the Effects of Melt–Mantle Interactions on the Gold Fertility of Magmas - Tassara, Santiago; Reich, Martin; Konecke, Brian A.; González-Jiménez, José María; Simon, Adam C.; Morata, Diego; Barra, Fernando; Fiege, Adrian; Schilling, Manuel E.; Corgne, Alexandre (Frontiers in Earth Science, 2020)
The oxidation state of the Earth’s mantle and its partial melting products exerts a fundamental control on the behavior and distribution of sulphur and chalcophile and siderophile elements between the mantle and crust, underpinning models of ore deposit formation. Whether the oxidized nature of magmas in inherited from the asthenospheric mantle source or acquired during ascent and differentiation is vigorously debated, limiting our understanding of the mechanisms of extraction of sulphur and metals from the mantle. Here, we focused on the redox-sensitive behavior of sulphur in apatite crystallized from quenched alkaline basaltic melts preserved within a peridotite xenolith from the El Deseado Massif auriferous province in southern Patagonia. We took advantage of this unique setting to elucidate the redox evolution of melts during their ascent through the subcontinental lithospheric mantle, and grasp the inner workings of the Earth’s mantle during gold metallogenesis. Our data reveal that an initially reduced silicate melt (ΔFMQ -2.2 to -1.2) was oxidized to ΔFMQ between 0 and 1.2 during percolation and interaction with the surrounding peridotite wall-rock (ΔFMQ 0 to +0.8). This process triggered changes in sulphur speciation and solubility in the silicate melt, boosting the potential of the melt to scavenge ore metals such as gold. We suggest that large redox gradients resulting from the interaction between ascending melts and the surrounding mantle can potentially modify the oxidation state of primitive melts and enhance their metallogenic fertility. Among other factors including an enriched metal source and favorable geodynamic conditions, redox gradients in the mantle may exert a first-order control on the global-scale localization of crustal provinces endowed with gold deposits.